2021
DOI: 10.1111/1365-2664.14064
|View full text |Cite
|
Sign up to set email alerts
|

Seed predation is key to preventing population growth of the weed Alopecurus myosuroides

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…It can be assumed that weed seeds remaining on the soil surface were exposed to fluctuating moisture and temperature conditions and to seed predation, both of which have a negative effect on seed longevity and on the probability of successful germination and plant establishment. A seed predation study, carried out at this experimental site in 2020, observed predation rates of around 89% of available seeds on the soil surface, irrespective of the soil tillage strategy (Daouti et al, 2022). Greater numbers of seeds remaining within the reach of seed predators in System C would partly explain the observed differences compared with Systems A and B.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that weed seeds remaining on the soil surface were exposed to fluctuating moisture and temperature conditions and to seed predation, both of which have a negative effect on seed longevity and on the probability of successful germination and plant establishment. A seed predation study, carried out at this experimental site in 2020, observed predation rates of around 89% of available seeds on the soil surface, irrespective of the soil tillage strategy (Daouti et al, 2022). Greater numbers of seeds remaining within the reach of seed predators in System C would partly explain the observed differences compared with Systems A and B.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, we assess the functional redundancy of the ecosystem function of weed seed predation and then explore how it is affected by agricultural intensity at the field scale and by landscape simplification. Predation of weed seeds by seed predators such as carabid beetles is an ecosystem function that contributes to biological weed control (Carbonne et al, 2020;Daouti et al, 2022). Functional redundancy of weed seed predation has never been directly quantified using field data, in part due to difficulties in specifying predator seed choices in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, seed predation and weed dynamics each respond to many interacting abiotic and management factors, and it is thus difficult to disentangle the highly variable seed predation among the many other factors affecting weed communities in the long term. This is the reason why several teams proposed models that synthesized the existing knowledge of environmental factors and management techniques on seed predation, and the latter's possible effects on weed dynamics (Westerman et al, 2003b;Davis et al, 2004;Westerman et al, 2005;Westerman et al, 2006;Daouti et al, 2022). However, none of these models includes sufficient weed and crop species, life-cycle processes and management techniques to actually simulate the impact of cropping systems on weed dynamics, let alone the consequences for crop production or biodiversity.…”
Section: Introductionmentioning
confidence: 99%